Perioperative sensor and algorithm programming in patients with implanted icds and pacemakers for cardiac resynchronization therapy - Niedermeier, Alexander; Vitali-Serdoz, Laura; Fischlein, Theodor; Kirste, Wolfgang; Buia, Veronica; Walaschek, Janusch; Rittger, Harald; Bastian, Dirk (Sensors, 2021)
Background: ICDs and pacemakers for cardiac resynchronization therapy (CRT) are complex devices with different sensors and automatic algorithms implanted in patients with advanced cardiac diseases. Data on the perioperative management and outcome of CRT carriers undergoing surgery unrelated to the device are scarce. Methods: Data from 198 CRT device carriers (100 with active rate responsive sensor) were evaluated regarding perioperative adverse (device-related) events (A(D)E) and lead parameter changes. Results: Thirty-nine adverse observations were documented in 180 patients during preoperative interrogation, which were most often related to the left-ventricular lead and requiring intervention/reprogramming in 22 cases (12%). Anesthesia-related events occurred in 69 patients. There was no ADE for non-cardiac surgery and in pacemaker-dependent patients not programmed to an asynchronous pacing mode. Post-operative device interrogation showed significant lead parameter changes in 64/179 patients (36%) requiring reprogramming in 29 cases (16%). Conclusion: The left-ventricular pacing lead represents the most vulnerable system component. Comprehensive pre and post-interventional device interrogation is mandatory to ensure proper system function. The type of ICD function suspension has no impact on each patient’s outcome. Precautionary activity sensor deactivation is not required for non-cardiac interventions. Routine prophylactic device reprogramming to asynchronous pacing appears inessential. Most of the CRT pacemakers do not require surgery-related reprogramming.
CRIS-Team Scopus Importer:2021-12-31
Keywords: Cardiac resynchronization therapy; Defibrillator shock; Electromagnetic interference; Heart failure; ICD; Implantable cardioverter defibrillator; Sensors; Sudden cardiac death